Transportation a global supply chain perspective - Novack, Robert A.; Gibson, Brian J.; Suzuki, Yoshinori; Coyle, John J. (Cengage Learning Asia, 2019)
Focuses on the widespread impact of commercial transportation on worldwide commerce